DEVELOPMENT OF MARINE ECOTOURISM WITH THE APPROACH OF SUITABILITY OF NATURAL RESOURCES AND CARRYING CAPACITY IN CEMARA BEACH, WAKATOBI: PENGEMBANGAN EKOWISATA BAHARI DENGAN PENDEKATAN KESESUAIAN SUMBERDAYA ALAM DAN DAYA DUKUNG DI PANTAI CEMARA WAKATOBI - Ardila, Ardila; Yulianda, Fredinan; Yulianto, Gatot (Jurnal Teknologi Perikanan dan Kelautan, 2026)
The Cemara Beach area on Wangi-Wangi Island has relatively high potential for biological resources. Coral reef ecosystems, reef fish, and capture fisheries reflect this potential. In addition to playing a crucial ecological role, these ecosystems also offer significant aesthetic value, making them an ideal asset for marine tourism. However, until now, the utilization of natural resources has not been regulated regarding site plan and visitor limitations, leading to the degradation of coral reef ecosystems. This study aims to determine the suitability classification and carrying capacity of marine ecotourism at Cemara Beach, Wangi-Wangi Island, Wakatobi, particularly for snorkeling and diving activities. Data collection was conducted in the reef flat zone and reef slope zone, selected through purposive sampling, which focused on the representation of the coral reef ecosystem using the manta tow method. The study showed that the location was highly suitable for marine ecotourism, in line with the high live coral cover (ranging from 46 to 76%), diversed types of life forms, abundant coral fishes, and high clarity of the waters. The carrying capacity for snorkeling activities is 240 people per day, within an area of 5.93 hectares, while diving activities have a utilization area of 1.83 hectares and a capacity of 60 people per day. Thus, the total carrying capacity for both activities is 300 people per day. To maintain the sustainability of coral reefs and marine tourism at Cemara Beach, sustainable tourism management is necessary through visitor capacity restrictions, zoning, and strict regulations.